53 Increasing staff confidence and competence to deliver individualised end of life care on elderly care wards: implementation of a symptoms observation chart and care plan guide. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Henderson, Daisy; Carey, Irene; Kennedy, Maggie; O'Driscoll, Gemma; Quraishi, Jasmine; Colebatch, Roxanna; Jones, Annabel; Patel, Radhika; Thomas, Emily
Abstract : Background: Following the withdrawal of the Liverpool Care Pathway concerns were expressed about staff confidence and competence to deliver end of life care. In response to locally identified needs and the recommendations for individualised care plans underpinned by the Five Priorities for Care of the Dying Person we have designed and implemented a Quality Improvement Project(QIP) within our NHS Foundation Trust. Method: We have introduced two tools, a symptom observation chart and care plan guide modelled on the Five Priorities. The tools were piloted initially on an acute medical admissions ward and have now been cascaded across four elderly care wards. Implementation was tracked and supported using QI methodology to include Run charts and PDSA cycles. Our aim is that all patients on elderly care wards who were recognised as being in the last days of life have 60% of their nursing care plans completed in line with the Five Priorities and 5/7 of symptoms listed on the symptom observation chart recorded and managed appropriately every 4 hours. Results: Over 22 weeks we identified 57 patients with End of Life Notifications. During this period 0%–70% of patients had 60% of their nursing care plans in line with the Five Priorities and 0%–100% of patients had 5/7 symptoms listed on the symptom observation chart recorded and managed appropriately every 4 hours. The variation in the use and completion of both tools may be explained to some extent by the small sample size and missing data (59% of charts in PDSA1 and 50% in PDSA2 were missing). Conclusion: Staff on these wards require ongoing education and efforts to promote engagement and investment in the tools. Data collection to assess the adherence to standards with regards to the timing of bedside assessments and escalation of concerns to senior staff where applicable is currently ongoing.